Taxonomic revision of the southamerican genus Picnoseus Solier (Coleoptera: Meloidae), including Pyrotini biogeographical considerations - Campos-Soldini, Maria P.; Safenraiter, Melania E.; Roig-Juñent, Sergio A. (Zootaxa, 2026)
The endemic South American genus Picnoseus Solier (Tenebrionoidea: Meloidae: Pyrotini) is revised. Picnoseus is distributed primarily in arid regions of the Andean Region, including Central Chile, and the Andean and Monte provinces. All known species have been comprehensively redescribed, incorporating detailed illustrations of the hindwing and genitalia of both sexes for the first time. Five new species from Chile are described, and an updated identification key is presented. Finally, the first biogeographic analysis of New World Pyrotini genera is conducted, with a focus on South American taxa to elucidate their evolutionary history.